Safety and Efficacy of Pamidronate in Neonatal Hypercalcemia Caused by Subcutaneous Fat Necrosis: A Case Report - Martinelli, Stefano; Pitea, Marco; Gatelli, Italo Francesco; Raouf, Tara; Barera, Graziano; Vitelli, Ottavio (Frontiers in Pediatrics, 2022)
Subcutaneous fat necrosis of the newborn (SCFN) is a panniculitis that develops in fatty areas after fetal or perinatal distress. Prognosis is generally good with complete regression, but it can be complicated by metabolic abnormalities like hypoglycemia, hypertriglyceridemia, thrombocytopenia, and also potentially life-threatening hypercalcemia. Treatments have included hydration, furosemide and corticosteroids. These treatments can be prolonged for several days and can have complications such as nephrocalcinosis. Use of bisphosphonates has been rarely reported in newborn. We describe a case of severe hypercalcemia complicating subcutaneous fat necrosis in a newborn successfully treated by a single dose of pamidronate after having obtained partial response by therapy with hyperhydration, furosemide and hydrocortisone. When high levels of calcium do not respond to first line therapy with hyperhydration and diuretic therapy, bisphosphonates treatment could be considered a valid choice to treat hypercalcemia and to avoid corticosteroids. Further studies are needed to understand if pamidronate and other bisphosphonates can be considered the first choice in hypercalcemia due to SCFN.